Foreign body in the region of the lower third molar: case report - Paltas Miranda, Mayra Elizabeth (2020)
Rotating instrument fracture is a rare trans-operation complication in third molar surgery. When it goes unnoticed, its diagnosis as a foreign body is usually a radiographic finding and its extraction requires careful evaluation. A clinical case of a 21-year-old female patient is presented, who comes to the Surgery service of the Faculty of Dentistry of the Central University of Ecuador (FOUCE), referred by the radiographic finding of a foreign body in the left posterior jaw, the history refers to the extraction of lower third molars 5 years ago; without clinical signs on intraoral examination, in the radiographic study the presence of a radiopaque shadow was observed in the distal part of dental organ # 37, confirmed on tomography as an image compatible with a fractional drill between the active and passive parts. The diagnosis was of an intra-osseous foreign body placed and divided into 2 fragments. The treatment consisted of the excision of the passive part of the drill; it was decided not to extract the active part located below the nervous-vascular package, due to the risk of injury to the lower dental nerve. In the post-operation period, clinical, radiographic and tomographic controls were performed, no complications were observed, the patient remained asymptomatic and stable.